ANALISA PEMANFAATAN M-COMMERCE UNTUK MENINGKATKAN KUNGGULAN BERSAING DI ERA INTERNET MOBILE MENGGUNAKAN METODE FIVE-FORCE MODEL (Studi Kasus Tokopedia.com) - Susiyanto, hendro (INDUSTRIKRISNA, 2024)
Since two decades, technology analysts predicted that mobile technology is the future, about how we conductbusiness in the era of a mobile internet. Analysts argue that mobile technology will be the backbone of electroniccommerce (e-commerce) and will change the economic environment to such an extent that "old economic rules willbecome obsolete" (Porter, 2001). Mobile technology opens new avenues for interaction between marketers andcustomers/buyers. Marketers are the first to take advantage of the opportunities that mobiletechnology offers, wherethey do business in a different way than before. However, adopting mobile technology does not necessarily guaranteesuccess. There are several aspects that need to be considered in the use of mobile technology in supporting marketing,especially by the new start-ups and or small and medium enterprises. This short paper tries to present a review ofsome concerns need to be considered in utilisizing mobile commerce, as well as some examples of start-ups counts successfully established in utilizing mobile technology for their marketing